Influence of compiler optimizations on system power - Kandemir, M.; Vijaykrishnan, N.; Irwin, M. J.; Ye, W. (37th Design Automation Conference, 2000, 2000)
High-level compiler optimizations ha ve been widely used to ac hiev e speedups on array-based codes. Su ch optimizations are becoming increasingly important in embedded signal processing and multimedia systems. The focus of these optimizations has traditionally been on improving performance. Ho w ev er, energy constraints are of critical importance in battery-operated embedded devices. In this paper, w e presen t an experimental evaluation of several state-of-the-art compiler optimizations on energy consumption, considering both the processor core (datapath) and memory system. This is in contrast to many of the previous works that ha ve considered them in isolation.